The g-C3N4 nanosheets decorated by plasmonic Au nanoparticles: A heterogeneous electrocatalyst for oxygen evolution reaction enhanced by sunlight illumination - Wang, Hairui; Sun, Tao; Chang, Limin; Nie, Ping; Zhang, Xuelin; Zhao, Cuimei; Xue, Xiangxin (Electrochimica acta, 2019)
A plasmonic-metal/semiconductor heterogeneous electrocatalyst composed of gold nanoparticles and graphitic carbon nitride sheets are prepared in this work for the purpose of showing off the improvement effect of surface plasmon resonance reinforcing photo-electro cooperation on the oxygen evolution reaction. It is found that gold nanoparticles with 15.3 nm average grain diameter are loaded on graphitic carbon nitride sheets forming a desirable plasmonic-metal/semiconductor structure. Under visible light illumination, the gold-graphitic carbon nitride catalyst exhibits a superior oxygen evolution reaction performance in alkaline electrolyte including a lower overpotential of 400 mV (10 mA cm−2 catalytic current density) and a smaller Tafel slope of 53 mV dec−1. And furthermore, the catalyst shows good stability. The improved oxygen evolution reaction property can be attributed to the synergistic effect between graphitic carbon nitride sheet and the gold nanoparticles under simulated sunlight illumination, including the photoelectric effect of graphitic carbon nitride sheet, the diffusion current drifting effect caused by the built-in electric field residing in the Schottky barrier zone (between the graphitic carbon nitride sheet and the gold nanoparticles), and most important, the surface plasmon resonance induced hot-electrons injection effect from plasmonic gold nanoparticles. [Display omitted] •Light illumination is available energy to improve OER catalytic activity.•Au/g-C3N4 heterogeneous catalyst exhibits superior OER activity under visible Light.•The plasmonic effects could be employed to enhance OER catalytic activity.